IL-9 promotes proliferation and metastasis of hepatocellular cancer cells by activating JAK2/STAT3 pathway - Lei, Rong-E (Int J Clin Exp Pathol, 2017)
The role of IL-9 in hepatocellular carcinoma (HCC) remains unknown. This study was designed to investigate the effect of IL-9 on HCC cells and the underlying signaling pathway. HCC cell lines SMMC-7721 was treated by IL-9, and the activities of cells were tested. The expression of JAK2, STAT3, p-JAK2 and p-STAT3 was detected by Western Blot assay. RT-PCR was used to detect the expression of MMP-2, MMP-9 and VEGF. SMMC-7721 cells were pre-treated with AG490, which is the inhibitor of JAK2/STAT3 pathway, and then incubated with IL-9. The expression of STAT3, p-STAT3, VEGF, MMP-2 and MMP-9 was detected, and the activities of SMMC-7721 cells was tested. The data showed that IL-9 significantly promoted the proliferation, invasion and migration of SMMC-7721 cells in a concentration dependent manner. Exposure to IL-9 increased the activation of p-STAT3 and p-JAK2, and increased the expression of MMP-2, MMP-9 and VEGF at the same time. Suppression of JAK2/STAT3 pathway by AG490 attenuated the promotive effects of IL-9 on SMMC-7721 cells, and reduced the expression of VEGF, MMP-2 and MMP-9. The present study demonstrated that IL-9 promotes the proliferation and metastasis in HCC cells and the effect may partly through the regulation of JAK2/STAT3 pathway.